Religious Moderation and Economic Growth in ASEAN: Potentials and Challenges for Inclusive Prosperity - Noval Noval; Nadia Nadia (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2025)
This study highlights the influence of religious moderation on economic growth and social stability in ASEAN, emphasizing the values of tolerance, inclusiveness, and justice as key drivers. Through in-depth literature analysis, the research finds that Islamic finance practices, such as sukuk, hold significant potential in driving regional economic growth, while the values of religious moderation also support sustainable economic sectors like tourism. Recommendations to enhance Islamic financial infrastructure, strengthen the tourism sector, and improve regional cooperation in trade and investment, along with the integration of environmental sustainability into economic policies, are expected to bolster inclusive and sustainable economic growth in ASEAN and improve the overall quality of life for its people.